Psychometric Validation of the Self-Efficacy for Restricting Dietary Salt in Hemodialysis Scale - Clark-Cutaia, Maya N. (Top Clin Nutr, 2013)
The development and progression of left ventricular hypertrophy is a consequence of multiple comorbid conditions associated with end-stage renal disease and large variations in interdialytic weight gains. The literature suggests that dietary sodium restriction alone significantly reduces interdialytic weight gains. A total of 124 hemodialysis participants in an ongoing randomized control trial participated in the validation in which psychometric properties of a self-efficacy survey were a secondary analysis. We evaluated the internal consistency, construct validity, and convergent validity of the instrument. The overall Cronbach α was 0.93. Three factors extracted explain 67.8% of the variance of the white and African American participants. The Self-Efficacy Survey has adequate internal consistency and construct and convergent validity. Future research is needed to evaluate the stability and discriminant validity of the instrument.